Pengaruh Harga dan Digital Marketing terhadap Minat Beli Konsumen pada Konveksi Tikasari Collection Larangan Kota Tangerang - Cornelia Dumarya Manik; Indah Septika Sari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
In today's competitive market, understanding factors that influence consumer behavior is crucial for businesses to enhance sales and customer loyalty. Price and digital marketing are considered pivotal elements that shape consumers’ purchasing decisions, especially in the fashion and retail industry. Therefore, this research seeks to provide empirical evidence on how these variables affect consumer buying interest in the context of a local convection business. This study aims to examine the effects of Price and Digital Marketing on Consumer Buying Interest at Tikasari Collection Convection in Tangerang, both partially and simultaneously. The research employs a quantitative approach using a survey method. The object of the study is Tikasari Collection Convection located in Tangerang, Indonesia, and the subjects are consumers actively making purchases there. A total of 91 respondents were selected using simple random sampling and were given structured questionnaires with closed-ended questions on a Likert scale. Data were analyzed using SPSS 26 with multiple linear regression analysis. The analysis involved descriptive statistics, validity and reliability tests, classical assumption tests, and finally, multiple linear regression to test the hypothesized relationships. The results indicate that both Price and Digital Marketing significantly influence Consumer Buying Interest. This finding emphasizes that competitive pricing strategies combined with effective digital marketing campaigns can boost consumer interest and potentially enhance sales performance. The study provides valuable insights for local businesses to prioritize these factors in their marketing strategy to attract and retain customers in a digitally evolving market environment.